Accessibility of Murabahah Financing for Coastal Fishermen (Systemic Approach in the Perspective of Maqashid al-Sharia) - Syarifa Fadlun (PALAPA, 2025)
East Lombok, a district in West Nusa Tenggara Province, has substantial marine and fisheries potential, particularly in the southern coastal areas of Jerowaru and Keruak, yet this potential remains underutilized due to limited access to financing mechanisms that match the socio-economic characteristics of fishing communities. Persistent poverty among small-scale fishermen is largely driven by difficulties in obtaining business capital from formal financial institutions because they do not possess the collateral required by conventional financing systems. This study aims to analyze an alternative microfinance model for fishermen based on Islamic law by employing qualitative field research that is conceptually grounded in Jasser Auda’s systems approach with its six epistemological dimensions: Cognitive, Purposefulness, Holism, Openness, Multidimensionality, and Dynamic. The analysis focuses on how a microfinance scheme structured through murabahah can address the technical constraints faced by fishermen and support the construction of legal provisions that realize jalb al-mashalih wa daf'u al-mafasid, thereby fostering stability, justice, and welfare in their lives. The findings underscore the potential of a systems-based Islamic microfinance model to better align financing schemes with the lived realities of coastal fishing communities, contributing to more equitable access to capital and to the broader objectives of social justice and economic well-being within the framework of Islamic law.